(untitled) (Academicia Globe: Inderscience Research, 2022)
In this article, there has been given practical and theoretical skills for masterfully performing works to musician. Moreover, the performer can also take the words which was written based on the experiences of great composers as a practical guide from this article. It is a fact that, if musicians fully use the theoretical knowledge in this article, they will achieve positive results in the process of performance. I believe that musicians will gain the necessary knowledge which they need from this article.